ANALISIS KEMAMPUAN SISWA BERPIKIR KRITIS MATEMATIKA PADA MATERI KUBUS DAN BALOK DI KELAS VIII SMP NEGERI 19 PERCONTOHAN BANDA ACEH - Umam, Khairul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Critical thinking is a mental activity undertaken to evaluate the truth of a statement. Generally the evaluation ends with a decision to accept, deny, or doubt the correctness of the statement in question. The ability of students in solving problems related to math is still low. This is due to the limited ability to memorize the concept or procedure to solve the problem in accordance with the given material. This study aims to determine student's mathematical critical thinking skills on cube and beam material in class VIII SMP Negeri 19 Pilot Banda Aceh. The approach used in this study is a qualitative approach. The type of this research is descriptive research. The research subjects are class VIII-2, which amounts to 21 students. While the object of research is the ability to think critically mathematics students on the material of cubes and beams. Data collection is done by performing student ability test to solve the problem of cube and beam. Problem given essay as much as 5 questions and interviews. The research data is sourced from result of student ability test and interview. Based on the results of research indicates that student's ability to think critically of mathematics is high. This is because students have met all the critical thinking stages, ranging from classification, assessment, inference, and strategy in solving the given problem. Students in this group know what information is contained in the problem, able to explain the purpose of the problem, can find steps to solve the problem, and even can find other ways to solve these problems. The result of this research is student's ability to think critically mathematics on material of cube and beam in class VIII SMP Negeri 19 Banda Aceh Pilot is high. where students are able to meet the four indicators of critical thinking namely classification, assessment, inference, and strategy.